Translocal strategies for experimenting with smart tourism labs in Zumaia: The case of the Basque Coast Geopark, Basque Country (Spain) - Calzada, I; Arranz, A (World Tourism Organization, 2018)
This paper presents a preliminary action research methodology based on living labs to overcome the current and simplistic one-size-fits-all big-data-driven smart tourism policy approach. Located in Zumaia, in the coast of the Basque Country (Spain), an experiment will be depicted innovative/democratic ways of touristic policy-making practices at the local level in respond to an increasing trend of visitors. Given the lack of attention about qualitative/ethnographic/strategic policy-making tools in the conventional governance realm, this paper shows a contextually-based living lab experimental methodology to co-create a prospective strategy building processes with local agents represented and fit in the multi-stakeholders Penta Helix framework.